2022
DOI: 10.3389/fphar.2022.907437
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM Structure and Activator Screening of Human Tryptophan Hydroxylase 2

Abstract: Human tryptophan hydroxylase 2 (TPH2) is the rate-limiting enzyme in the synthesis of serotonin. Its dysfunction has been implicated in various psychiatric disorders such as depression, autism, and bipolar disorder. TPH2 is typically decreased in stability and catalytic activity in patients; thus, screening of molecules capable of binding and stabilizing the structure of TPH2 in activated conformation is desired for drug development in mental disorder treatment. Here, we solved the 3.0 Å cryo-EM structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
1
0
0
Order By: Relevance
“…The dynamic behavior of the RDs is consistent with the monomer-dimer equilibrium of NΔ47-TPH2-RC observed by Tidemand et al 14 . Additionally, our observation is in agreement with a study from Zhu et al, who found that the RDs of an N-terminally tagged full-length TPH2 variant were too dynamic to be observed in their cryo-EM structure of the TPH2 tetramer 34 . Comparing the 2D class averages from the grids without L-Phe (Figure 5D) to the 2D classes with 50 μM L-Phe, did not reveal any significant differences in the overall structure, (Figure 5C-D).…”
Section: Resultssupporting
confidence: 93%
“…The dynamic behavior of the RDs is consistent with the monomer-dimer equilibrium of NΔ47-TPH2-RC observed by Tidemand et al 14 . Additionally, our observation is in agreement with a study from Zhu et al, who found that the RDs of an N-terminally tagged full-length TPH2 variant were too dynamic to be observed in their cryo-EM structure of the TPH2 tetramer 34 . Comparing the 2D class averages from the grids without L-Phe (Figure 5D) to the 2D classes with 50 μM L-Phe, did not reveal any significant differences in the overall structure, (Figure 5C-D).…”
Section: Resultssupporting
confidence: 93%